Sterilization of sea lice eggs with ultraviolet C light: towards a new preventative technique for aquaculture. Issue 3 (3rd October 2019) - Barrett, Luke T; Pert, Cassandra G; Bui, Samantha; Oppedal, Frode; Dempster, Tim
Abstract: BACKGROUND: Sea lice infestations on Atlantic salmon ( Salmo salar ) farms are a considerable burden on the industry and put wild salmonid populations at risk. Frequent delousing treatments are necessary to keep lice densities below allowable limits, but currently viable treatments have drawbacks in terms of financial cost, animal welfare, or environmental impacts. We tested if 254 nm ultraviolet C light (UVC) could function as a new preventative method to suppress reproduction of salmon lice ( Lepeophtheirus salmonis ) by sterilizing fertilized eggs. We exposed salmon lice eggstrings to a range of UVC intensities and durations to identify effective doses. RESULTS: A cumulative dose of 0.008 J cm −2 induced 5% egg mortality, while 95% egg mortality occurred at 0.09 J cm −2, indicating that UVC can be effective as a preventative treatment. The total cumulative dose appeared to be more important than the duration or number of individual exposures by which the total dose was achieved. CONCLUSION: UVC treatment has immediate applications for the salmon aquaculture industry, including for the treatment of wastewater from delousing or other operations. Future work will assess the feasibility of UVC dose delivery on host salmon in sea cage environments that involves little or no fish handling and creates negligible environmental impacts. © 2019 Society of Chemical Industry Abstract : New methods are needed to prevent and control sea lice infestations in salmon aquaculture. This article presents a test of ultraviolet C irradiation for reproductive suppression in sea lice.